Synthesis and Characterization Nanosilica from Rice Husk Ash Using Sol-Gel Method with Addition Of PEG-6000 and PVA - Dwi Rasy Mujiyanti; Uripto Trisno Santoso; Mutiara Dwi Saptarini; Nur Heirani Emi (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
Nano-silica (NS) from rice husk ash was successfully synthesized using a sol-gel process with the addition of polyethylene glycol (PEG) 6000 and polyvinyl alcohol (PVA) as a template. The purpose of this study is to investigate the properties of NS functional groups and the effect of PEG6000 and PVA concentrations (5%, 10%, and 15% (b / v)) on the size, morphology, and distribution of nanosilica. The functional groups of NS are characterized by Fourier transform infrared (FTIR), the size and morphology of NS are characterized by scanning electron microscopy (SEM). In contrast the size analyzer characterizes the particle size distributionof particulate matter (PSA). The results indicated that the addition of PEG-6000 and PVA affected the size and morphology of NS. The FTIR spectra showed the presence of silanol (Si-OH) and siloxane (Si-O-Si) groups. According to the SEM results, the morphology of NS -PEG is round and relatively more uniform than the amorphous morphology of NS-Control and NS-PVA. Instead of PEG-6000, Sol-gel PVA can be obtained with a narrow particle size distribution.